Article RETRACTED due to malpractice Knowledge, Awareness, and Risk Factors of Posterior Cruciate Ligament (PCL) Injuries Among Athletes in the Aseer Region: A Cross-Sectional Study - Khan, Muhammad Abid; Alshahrani, Ali Thamer Ali; Dareni, Mohammed Hussain; Alshahrani, Fahad Shari; Al-shahrani, Abdulmohsen Saeed; O Alhussain , Meshal Mohammed; AlMansour , Muidh Abdullah; Alquraish, Hussam Saeed D (Retos, 2026)
The largest and most intricate joint in the body is the knee. is the joint that young athletes sustain injuries to the most frequently . Conservative measures such as rest, ice, immobilization, and physical therapy can be used to treat the great majority of knee problems. The knee joint is stabilized by the posterior cruciate ligament (PCL), an extra-synovial, intra-articular ligament. It serves as a secondary restraint on internal rotation and the major restraint on posterior tibial translation. PCL tears are serious injuries that could have long-term effects on the knee joint.